Results of Competence Based Training in the Modules Related to "Algorithms and Data Structures" in the Profession of "Application Programmer" - Mollov, Muharem Asanov; Stoitsov, Gencho (TEM Journal, 2022)
The article describes a pedagogical research, conducted to determine the benefits of Competence Based Training (CBT) as part of a more general paradigm for Competence based education (CBE), in the modules related to Algorithms and data structures (ADS) in the profession of "Application programmer (occupation “Application programmer”). For the purposes of the study, CBT was conducted in several groups under the National Program "IT Career Training" (NPITC). A comparison was made with groups from the regular form of training in the same profession, where a traditional approach to education is applied. The results of the study show that the implementation of CBE under the National Program "IT Career Training" provides no worse training than the traditional approach used in vocational schools. Even in the study area of Algorithms and data structures, the experimental group showed significantly better results than the control group, which means achieving a higher level of acquiring knowledge and skills, as well as more successful formation of specific competencies to work with ADS and application of the paradigms FPS (Functional programming style) and OOP (Objectoriented programming).